REM sleep behavior disorder portends poor prognosis in Parkinson's disease: A systematic review. (January 2018) - Kim, Yoon; Kim, Young Eun; Park, Eun Ok; Shin, Chae Won; Kim, Han-Joon; Jeon, Beomseok
Highlights: RBD in PD means more than screaming at night and having reduced quality of life. Baseline RBD confers a higher risk of developing dementia and hallucinations in PD. RBD in PD entails a greater disease burden as exemplified by autonomic dysfunction. Evidence supports diffuse pathology extending beyond the brainstem in RBD in PD. Abstract: REM sleep behavior disorder (RBD) is a parasomnia wherein a loss of REM sleep atonia manifests as dream-enactment, often violent. Aside from its significance as a predictor of PD, RBD in PD may imply more than merely screaming at night and experiencing sleep fragmentation. To probe its significance as a prognostic factor in PD, we performed a systematic literature review. Analysis of prospective studies reveals baseline RBD confers a higher risk of developing dementia and hallucinations. In cross-sectional studies, RBD is associated with the non-tremor predominant motor phenotype and autonomic dysfunction. Clinical, imaging, and autopsy studies support the presence of dense and diffuse pathology extending beyond the brainstem in PD with RBD. As RBD in PD is associated with a greater disease burden and an increased risk of mortality, we propose the RBD subtype in PD to highlight that RBD may mark a distinct subtype with relatively poor prognosis.